Kecemasan dengan Persepsi Terhadap Peran Ibu pada Ibu Bekerja - Firdaus, Faradillah (Indonesian Journal of Social and Educational Studies, 2025)
Abstract. This study aims to examine the relationship between anxiety and perceptions of maternal roles among working mothers. The research employed a quantitative correlational design with 50 working mothers as participants. Data collection used anxiety scales for working mothers and maternal role perception scales, each consisting of 29 items with Likert scale format (0-3). Data analysis employed Pearson product-moment correlation. Results showed that working mothers have moderate anxiety levels (M=8.00, SD=2.68) and relatively positive perceptions of maternal roles (M=8.96, SD=2.01). Correlation analysis revealed a weak negative relationship (r=-0.215) that was not statistically significant (p>0.05). The coefficient of determination (R²=0.046) indicates that anxiety explains only 4.63% of the variance in maternal role perceptions. These findings suggest that maternal role perceptions are influenced more by other factors than anxiety levels, demonstrating the resilience of working mothers in maintaining positive role perceptions despite experiencing anxiety.Keywords: anxiety; maternal role perception; working mothers; dual roles; resilience